PENGARUH INDEPENDENSI, KOMPETENSI, PENGALAMAN TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Pada Kantor BPKP Provinsi Jawa Tengah) - Fauzy Arie Sandy, 14.05.52.0031; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the influence of independence, competence, experience on quality with auditor ethics as a moderating variable. The population in this study is the auditor who works in the Central Java Province BPKP Office. Sampling was done using the Convenience sampling method and the number of samples was 55 respondents. The primary data collection method used is the questionnaire method. And the data analysis uses multiple linear regression models. The results of this study indicate that independence, competence, and experience have a significant positive effect on audit quality. While audit quality is proven to moderate independence and experience on audit quality. But the auditor's ethics do not moderate the relationship of competence to audit quality. Keywords: Independence, competence, accountability, time budget pressure and audit quality